Inference in Regression Discontinuity Designs with a Discrete Running Variable - Michal Kolesár; Christoph Rothe (Institute for the Study of Labor (IZA), 2016)
We consider inference in regression discontinuity designs when the running variable only takes a moderate number of distinct values. In particular, we study the common practice of using confidence intervals (CIs) based on standard errors that are clustered by the running variable. We derive theoretical results and present simulation and empirical evidence showing that these CIs have poor coverage properties and therefore recommend that they not be used in practice. We also suggest alternative CIs with guaranteed coverage properties under easily interpretable restrictions on the conditional expectation function.
Keywords: C13; C14; C21; C25; 330; regression discontinuity design; discrete running variable; clustered standard errors